A team decision framework for quality decision outcomes. - Klass, Des; Schmidenberg, O.; DeReuck, J. (2005)
This paper outlines the Team Decision Framework which follows on from our previous work on optimising the quality of decision-making in groups.The TDF is proposed as a model of the skills and abilities which we have termed 'intelligences' that should ideally be present in order for groups making decisions to achieve their full potential. The paper describes the intelligences and outlines the development of the measuring instrument,using Structural Equation Modelling and exploratory factor analysis. The TDF is designed to profile groups' decision-making capabilities. It is anticipated that such profiling might be used for diagnostic, training and comparative research purposes.